Cerium-doped mesoporous-assembled SiO2/P25 nanocomposites with innovative visible-light sensitivity for the photocatalytic degradation of organic dyes. Issue 21 (24th February 2017) - Jiang, Yan; Jin, Zheng; Chen, Chen; Duan, Wubiao; Liu, Bo; Chen, Xidong; Yang, Feihua; Guo, Jianping
Abstract : Photocatalytic mechanism for the photodegradation of organic dyes over a Ce–SiO2 /P25 catalyst under visible light. Abstract : SiO2 /P25 (SP) composites doped with different contents of cerium were prepared by a hydrothermal process at a relatively low temperature in this experiment. The resulting Ce–SiO2 /P25 (CSP) composites were successfully characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), high resolution transmission electron microscopy (HRTEM), N2 -physisorption, UV-vis diffuse reflectance spectroscopy (DRS), and photoluminescence spectroscopy (PL). The photocatalytic activities of the as-obtained catalysts were evaluated for the degradation of organic dyes, including Methylene Blue (MB) and Reactive Red 4 (RR4), under visible-light irradiation. The best results were obtained for a cerium loading of 5 mM. The CSP-5 nanoparticle showed the 91.8% decomposition of MB and 90.2% decomposition of RR4 in the liquid phase at room temperature under visible-light irradiation in a photoreactor, and the corresponding hydrogen evolution rate was 2.315 mmol g −1, which was more efficient than that of pristine P25. Remarkably enhanced activities towards the photodecomposition of several organic compounds were observed depending on the synergistic effect between silicon and cerium. The Ce–SiO2 /P25 structure leads to efficient light harvesting into the visible-light region by forming new energy levels inside the nanoparticles and then electron–hole recombination could be effectively inhibited. The BET surface area measurement was used to provide an insight into the enhanced photocatalytic activity of the CSP composites, which was also understood to be because of the relative enhancement of the adsorption of organic molecules on the photocatalyst surface. In addition, the effect of the initial pH values on the photocatalytic degradation of different dyes using CSP-5 was investigated. Finally, a good recyclability of CSP-5 was demonstrated compared to that of pristine P25. Herein, the photocatalytic mechanism has been concretely explained.